Civil Identity of Young Kazakhstanis in the Context of the Russian-Ukrainian Conflict - Assyltayeva, Elnura; Tarman, Bulent; Ishmukhamedov, Sharip; Mukhambedyarova, Altynai; Tolen, Zhengisbek; Yussupova, Saule (Journal of Ethnic and Cultural Studies, 2024)
The aim of this study is to conduct a sociological survey to assess the state of civic identity among Kazakhstani youth within the ongoing conflict between Russia and Ukraine. It aims to explore the correlation between young citizens' ethnic backgrounds and their acceptance of citizenship. Data was collected through a questionnaire developed by researchers to examine the multifaceted dynamics involved. A total of 754 citizens between 14 and 35 took part in the survey. The findings indicate that, in the present circumstances, the sense of belonging to the state among young Kazakhstanis is primarily contextual, prevailing over other identity constructs when queried about their attitude towards citizenship. However, when measuring the level of identification—how frequently individuals perceive themselves as citizens—ethnic identity takes precedence over civic identity. The survey underscores that ethnic origin stands out as the foremost determinant of social belonging for young people in Kazakhstan in the current scenario. Moreover, this study emphasizes the significant role played by information sources in shaping civic identity. We have elucidated the intricate relationship among ethnic identity, citizenship perception, and contextual factors among Kazakhstani adolescents amidst ongoing geopolitical events using our analytical approach.